UV Screening in Native and Non-native Plant Species in the Tropical Alpine: Implications for Climate Change-Driven Migration of Species to Higher Elevations - Barnes, Paul W.; Ryel, Ronald J.; Flint, Stephan D. (Frontiers in Plant Science, 2017)
Ongoing changes in Earth’s climate are shifting the elevation ranges of many plant species with non-native species often experiencing greater expansion into higher elevations than native species. These climate change-induced shifts in distributions inevitably expose plants to novel biotic and abiotic environments, including altered solar ultraviolet-B (UV-B; 280-315 nm) radiation regimes. Do the greater migration potentials of non-native species into higher elevations imply that they have more effective UV-protective mechanisms than native species? In this study, we surveyed leaf epidermal UV-A transmittance (TUVA) in a diversity of plant species representing different growth forms to test whether native and non-native species growing above 2,800 m elevation on Mauna Kea, Hawaii differed in their UV screening capabilities. We further compared the degree to which TUVA varied along an elevation gradient in the native shrub Vaccinium reticulatum and the introduced forb Verbascum thapsus to evaluate whether these species differed in their abilities to adjust their levels of UV screening in response to elevation changes in UV-B. For plants growing in the Mauna Kea alpine/upper sub-alpine, we found that adaxial TUVA, measured with a UVA-PAM fluorometer, varied significantly among species but did not differ between native (mean=6.0%; n=8) and non-native (mean=5.8%; n=11) species. When data were pooled across native and non-native taxa, we also found no significant effect of growth form on TUVA, though woody plants (shrubs and trees) were represented solely by native species whereas herbaceous growth forms (grasses and forbs) were dominated by non-native species. Along an elevation gradient spanning 2,600-3800 m, TUVA was variable (mean range = 6.0-11.2%) and strongly correlated with elevation and relative biologically effective UV-B in the exotic V. thapsus; however, TUVA was consistently low (3%) and did not vary with elevation in the native V. reticulatum. Results indicate that high levels of UV protection occur in both native and non-native species in this high UV-B tropical alpine environment, and that flexibility in UV screening is a mechanism employed by some, but not all species to cope with varying solar UV-B exposures along elevation gradients.